Triage process in Emergency Departments: an Indonesian Study - Rochana, Nana; Morphet, Julia; Plummer, Virginia (Department of Nursing, Faculty of Medicine, Diponegoro University, 2016)
Background: Triage process has rapidly developed in some countries in the last three decades in order to respond to the demand for emergency services by growing population and emergency health needs. However, this development does not appear to match in Indonesian hospitals. The triage process in Indonesia remains obscure.Purpose: This study aimed to describe triage process in Indonesia from a range of different perspectives.Methods: The research design of this study was descriptive qualitative using semistructured interviews of 12 policy makers or persons responsible from 5 different organizations which informed triage practice in Indonesia. The data were analyzed using a three step content analysis.Results: The result produced 3 themes. First, four steps of triage process ranging from receiving to prioritizing were reported as the triaging procedures in Indonesia which were almost similar to the international literature except for a re-triage step. Second,primary and secondary triage processes were also applied in all emergency departments in Indonesia. Last, no prolonged waiting time in Indonesia could be assumed whether the triage process was effective and efficient or it was only a quick process of sorting to rapidly increase the number of patients in the treatment rooms. Out of the themes, the result also indicated that the involvement of nurses in health policy development inIndonesia needed supportConclusion: Triage process in Indonesia still needs improvements. Patient’s re-triage and evaluating secondary triage should be given more frameworks in the future. An effective and efficient triage process in Indonesia will best manage the number of patients in the treatment rooms and therefore further observational researches on patterns and trends are needed. Moreover, including the role of nurses as policy makers in the curriculum of nursing undergraduate and post-graduate degrees would give nurses the evidence to seek out policy making positions in the future